Apple Training Series GarageBand 3 - Plummer, Mary (Peachpit Press, 2006)
Whether you're an accomplished musician or a student, Garageband is the most rewarding way to create, perform, and record your own music. In the only Apple-certified guide to Garageband, composer and master trainer Mary Plummer shows you just how easy it is to turn your Mac into a fully featured recording studio. Plummer offers a complete, self-paced course in all aspects of Garageband - from mastering the interface and basic recording techniques to the secrets of arranging a song, editing and mixing tracks, adding effects, and distributing your Garageband compositions. Fully updated for version 3, Mary covers all of Garageband's hot new features including podcast recording and iMovie scoring.